2002
DOI: 10.1089/107555302760253649
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Evaluation of the Efficacy and Safety of Cogent db (an Ayurvedic Drug) in the Glycemic Control of Patients with Type 2-Diabetes

Abstract: These results concur with earlier animal studies that indicate that Cogent db is safe, reliable, tolerable, and efficacious in the control of type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…In contrast, based on the present morphometric and morphological findings, we suggest that the test botanical drug (A. indica) is capable of enhancing b-cell proliferation in vivo. Our findings provide morphologic evidence supporting the tradomedical use of this drug as an antidiabetic therapy (Abo et al, 2008), as well as its current use in certain antidiabetic formulations (Shekhar et al, 2002;Hsia et al). Similar morphological improvement of the pancreatic islets had been reported in studies that employed the tetrapeptide pancreagene (Kvetnoi et al, 2007), the angiotensinconverting enzyme inhibitor ramipril (Ko et al), and the herbal drugs dangnyosoko (Kim et al, 2007), hachimi-jiogan (Yamabe & Yokozawa), and Aloe vera (Noor et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, based on the present morphometric and morphological findings, we suggest that the test botanical drug (A. indica) is capable of enhancing b-cell proliferation in vivo. Our findings provide morphologic evidence supporting the tradomedical use of this drug as an antidiabetic therapy (Abo et al, 2008), as well as its current use in certain antidiabetic formulations (Shekhar et al, 2002;Hsia et al). Similar morphological improvement of the pancreatic islets had been reported in studies that employed the tetrapeptide pancreagene (Kvetnoi et al, 2007), the angiotensinconverting enzyme inhibitor ramipril (Ko et al), and the herbal drugs dangnyosoko (Kim et al, 2007), hachimi-jiogan (Yamabe & Yokozawa), and Aloe vera (Noor et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…A. indica is currently included in polyherbal antidiabetic drugs being subjected to controlled clinical trials in human (Hsia et al, 2004;Shekhar et al, 2002). However, histopathological changes of the pancreatic islets, which may be associated with chronic exposure to A. indica as an antidiabetic therapy, are yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…We identified seven other studies (Crawford 2009;Dubey 1993;Faizal 2009;Maji 1995;Mohan 1998;Poongothai 2002;Yadav 2001) through additional searches, out of which four (Crawford 2009, Dubey 1993Mohan 1998;Poongothai 2002) were found eligible for inclusion. After feed back from peer reviewers, it was decided to exclude 16 studies of single herbs (Altschuler 2007;Anderson 1999;Aro 1981;Blevins 2007;Cohen 1980;Crawford 2009;Gupta 2001;Holman 1987;ICMR Study Group 2005;Kuriyan 2008;Lalor 1990;Mang 2006;Niemi 1988;Uusitupa 1984;Uusitupa 1989;Ziai 2005) and hence only seven studies were ultimately included in the final analysis (Agrawal 2002;Dubey 1993, Elder 2006Mohan 1998;Poongothai 2002;Shekhar 2002). An adapted PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow-chart of study selection is attached Figure 1 Included studies…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Some traditionally used herbs and plants have been more rigorously tested in double-blind controlled trials than others and the following appear promising: Coccinia indica, Momordica charantia, Gymnema sylvestre, Panax quinquefolius, Opuntia streptacantha, and Aloe vera (Table 1) [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Nevertheless, further testing is necessary within the scientific context to assess efficacy, safety, and mechanism of action.…”
Section: Complementary and Alternative Herbal Remediesmentioning
confidence: 99%
“…This mixture contains A. indica, Phyllanthus emblica, Curcuma longa, T. foenum-graecum, Syzygium cumini, Tribulus terrestris, Terminalia belerica, Terminalia chebula, and Routula aquatica [44]. One controlled study treated patients with type 2 diabetes with cogent db for 3 months and showed significant improvements in fasting plasma glucose and A 1c levels (220 to 158 mg/dL and HbA 1c 10.2% to 8.3%, P < 0.001).…”
Section: Herbal Combinationsmentioning
confidence: 99%